Origem e desenvolvimento da comunidade de professores de Física em Belo Horizonte na primeira metade do século XX - Ely Roberto da Costa Maués (2023)
This doctoral research aimed to investigate the constitution of the community of Physics teachers in Belo Horizonte, during the first half of the 20th century. With this study, I sought to understand the social context in which the group of teachers was inserted, their difficulties and challenges, as well as the collective and individual actions that led to the transformations and reconfigurations of practices in teaching Physics, in addition to the legacy left by these subjects. The investigated group is composed of professors who stood out in the community of Physics teachers in Belo Horizonte, and who joined the teaching profession between the 1920s and 1950s, contributing significantly to the production of didactic materials, introduction of new teaching and training experiences. of new disciples. This period marks the first movements for the development of research in Physics, through the creation and implementation of Licentiate and Bachelor of Physics courses at the Faculty of Philosophy, Sciences and Letters of Minas Gerais. To carry out the research, the methodological approach of narrative investigation and data sources such as professional life history interviews were used. Part of the data was collected by the author in interviews with the subjects, part was extracted from oral history interviews, published in periodicals, videos and from biographies already produced by third parties. The theoretical foundation of the research is based on studies of community of practice, especially on the works of Etienne Wenger. The research's contributions include addressing issues little explored in the historiography of Brazilian Education, such as the origin and development of disciplinary communities of teachers. The thesis defended by the research is that the investigated group can be characterized as a community of practice of Physics teachers, since it was possible to verify the three constitutive elements of the social theory of learning proposed by Wenger, which are the domain, the community and the practice. The construction of this argument allowed for a deeper understanding of the contributions of a generation of teachers from Belo Horizonte who were pioneers in the creation and development of physics in the first half of the 20th century. The analyzes indicate that, for the constitution of this community, the initial convergence of the subjects on the challenges posed to the teaching of physics was essential, which enabled the creation of working ties and mutual trust, identification of physics as a science and the defense of its experimental nature. The long-term perspective of collective work also showed the community's ability to incorporate and respect the subjects' own paths, both in teaching and in research. The findings reveal a richer, more complex and challenging educational reality in the period studied, which is still little evidenced in the hegemonic description of the history of science teaching in Brazil.